Facile approaches to prepare n-ZnO/(i-ZnO)/p-GaN heterojunction light-emitting diodes with white-light-electroluminescence. (6th November 2019) - Huo, Chunqing; Lu, Youming; Zeng, Hua; Cao, Peijiang; Han, Shun; Liu, Wenjun; Jia, Fang; Zeng, Yuxiang; Liu, Xinke; Xu, Wangying; Zhu, Deliang
Abstract: White-light-emitting diode (LED) with effective energy conservation and long service life could be employed in numerous applications. In this study, the high-performance n-ZnO films were first prepared via pulsed laser deposition on p-GaN substrates and then the n-ZnO/p-GaN heterojunction LED was fabricated. This LED exhibits blue and yellow light emission, and their emission intensities can be tuned by adjustment of the fabrication parameters (e.g. oxygen pressure) and/or by introduction of a semi-insulating i-ZnO layer to form a p-GaN/i-ZnO/n-ZnO heterojunction. Thus, a facile approach has been proposed for the preparation of white LED.